Aimless Agency: Religious Engagement in an Uncertain World. (19th July 2022) - Cassaniti, Julia L.; Chladek, Michael R.
Abstract: Bronislaw Malinowski suggested nearly a century ago that a key purpose of religious engagement is to provide a sense of stability in the face of uncertainty. This close relationship between religion and stability is often presumed by scholars today, but, we argue, it is not as universal as is often supposed. Drawing on over 15 years of ethnographic research in Northern Thailand, we show how Thai Buddhists actively and strategically remind themselves of the inherent precarity of the future, rather than seek to minimize it. Analyzing rhetoric that draws on shared understandings of the uncertain in day‐to‐day religious practice, we show how Thai Buddhists strive for what we call "aimless agency": a psychological acceptance of future unknowability. We use this ethnographic example to suggest further work on the social implications of impermanence and the importance of paying greater attention to cultural variability in religious approaches to an uncertain world.